Calreticulin secures calcium-dependent nuclear pore competency required for cardiogenesis. (March 2016) - Faustino, Randolph S.; Behfar, Atta; Groenendyk, Jody; Wyles, Saranya P.; Niederlander, Nicolas; Reyes, Santiago; Puceat, Michel; Michalak, Marek; Terzic, Andre; Perez-Terzic, Carmen
Abstract: Calreticulin deficiency causes myocardial developmental defects that culminate in an embryonic lethal phenotype. Recent studies have linked loss of this calcium binding chaperone to failure in myofibrillogenesis through an as yet undefined mechanism. The purpose of the present study was to identify cellular processes corrupted by calreticulin deficiency that precipitate dysregulation of cardiac myofibrillogenesis related to acquisition of cardiac phenotype. In an embryonic stem cell knockout model, calreticulin deficit ( crt − / − ) compromised nucleocytoplasmic transport of nuclear localization signal-dependent and independent pathways, disrupting nuclear import of the cardiac transcription factor MEF2C. The expression of nucleoporins and associated nuclear transport proteins in derived crt − / − cardiomyocytes revealed an abnormal nuclear pore complex (NPC) configuration. Altered protein content in crt − / − cells resulted in remodeled NPC architecture that caused decreased pore diameter and diminished probability of central channel occupancy versus wild type counterparts. Ionophore treatment of impaired calcium handling in crt − / − cells corrected nuclear pore microarchitecture and rescued nuclear import resulting in normalized myofibrillogenesis. Thus, calreticulin deficiency alters nuclear pore function and structure, impeding myofibrillogenesis in nascent cardiomyocytes through a calcium dependent mechanism. This essential role of calreticulin in nucleocytoplasmic communication competency ties its regulatory action with proficiency of cardiac myofibrillogenesis essential for proper cardiac development. Highlights: Calreticulin-deficient ( crt −/− ) embryonic stem cells (ESCs) exhibit nuclear flaws. Dysfunctional nuclear pore complex (NPC) remodeling occurs in crt −/− ESCs. Impaired nuclear import in crt −/− ESCs drives aberrant cardiogenesis. Rectified crt −/− ESC calcium dynamics corrects NPC, cardiophenotype abnormalities. Calcium-dependent crt-NPC signaling is a novel cardiac differentiation regulator.